Reduction of Constraints on Arbitrage Trading and Market Efficiency: An Examination of Ex‐Day Returns in Hong Kong after Introduction of Electronic Settlement - Kadapakkam, Palani‐Rajan (Journal of Finance, 2000)
Previous research documents positive ex‐dividend day returns in excess of one percent in the unique institutional setting of Hong Kong, where neither dividends nor capital gains are taxed. Short‐term arbitrage trades around the ex‐day were hampered by physical settlement procedures. After the recent switch to an electronic settlement system, which enables such trades, ex‐day abnormal returns have declined to an insignificant 0.17 percent. This drop is more pronounced for high‐yield stocks, which are more likely to attract dividend capture trading. The evidence points to the crucial role of short‐term traders in ensuring the pricing efficiency of financial markets.